1998
DOI: 10.1021/ja9742904
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterization of Dendrimer Monolayers and Dendrimer−Alkanethiol Mixed Monolayers Adsorbed to Gold

Abstract: Single-component monolayers of dendrimers and two-component monolayers consisting of dendrimers and n-alkanethiols immobilized on Au substrates are described. Single-component monolayers are prepared by exposing an Au substrate to ethanolic solutions of amine- or hydroxy-terminated polyamidoamine (PAMAM) dendrimers. The resulting monolayers are highly stable and nearly close-packed for dendrimer generations ranging from 4 to 8 (G4−G8). Electrochemical ac-impedance measurements indicate that the dendrimer surfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

26
239
4
2

Year Published

1999
1999
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 232 publications
(272 citation statements)
references
References 58 publications
26
239
4
2
Order By: Relevance
“…Indeed, computer simulations of DPs with a relatively low number of repeat units (i.e. [25][26][27][28][29][30] show end cap effects (results not shown) that resemble the deformability of dendrimers adsorbed on surfaces. In these DPs dendrons located at the two ends tend to use the available space and the hemispherical end caps to align in the direction of the macromolecular backbone, whereas in adsorbed dendrimers at low g dendrons tend to occupy the spherical free volume around the core 17 to form very flat structures.…”
Section: Resultsmentioning
confidence: 98%
“…Indeed, computer simulations of DPs with a relatively low number of repeat units (i.e. [25][26][27][28][29][30] show end cap effects (results not shown) that resemble the deformability of dendrimers adsorbed on surfaces. In these DPs dendrons located at the two ends tend to use the available space and the hemispherical end caps to align in the direction of the macromolecular backbone, whereas in adsorbed dendrimers at low g dendrons tend to occupy the spherical free volume around the core 17 to form very flat structures.…”
Section: Resultsmentioning
confidence: 98%
“…24,25 The terminal groups of the immobilized dendrimers can be postfunctionalized easily without their loss from the surface. 24 A computer based simulation of the dendrimer monolayer formation has revealed that the high-generation dendrimers tend to flatten and spread on the surface, while the lowgeneration dendrimers, such as generation 1 (G1) or G2, retain their bulk-phase conformation, but are less immobilized. 23 Therefore, we assumed that G3 or G4 dendrimers retain the three-dimensional identity of dendrimers with high immobilization when forming the monolayer on the solid support.…”
Section: Resultsmentioning
confidence: 99%
“…The diameters of PAMAM G3 and G4 dendrimers are ~40 Å and ~50 Å, and the number of their terminal amine groups are 32 and 64, respectively. 24 The proposed model of molecular ordering assumes that they have highly deformed ellipsoidal shapes in condensed monolayers. 24,25 The coupling with PDC at the terminal end increases the diameter by ~17 Å.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have taken refractive index for biomolecules equal to 1.46 [38,39]. Refractive index for water was estimated by the equation adopted from [40] …”
Section: Theorymentioning
confidence: 99%